Guidelines for Developing the Quality of Life of Police Officers under the Phetchaburi Provincial Police - Powsri, Sarach; Adulbutra, Suchart; Maitreesopho, ฺBampen (Journal of Social Sciences and Humanities Research in Asia, 2025)
Police officers frequently face a wide range of evolving crime-related challenges, including stress and pressure stemming from both their professional duties and personal lives. This mixed-method study aimed to: 1) assess the quality of life of police officers under the Phetchaburi Provincial Police; 2) compare perceptions of quality of life among officers based on their personal characteristics; 3) examine work-related factors that influence quality of life; and 4) propose guidelines to improve the quality of life of police officers. The quantitative component involved a sample of 300 police officers, with data analyzed using frequency, percentage, mean, standard deviation, one-way ANOVA, and multiple regression analysis. The qualitative component included nine key informants, with data collected through in-depth interviews and analyzed using thematic analysis. The findings revealed that: 1) the overall quality of life of police officers was rated at a high level; 2) there were no statistically significant differences in perceptions of quality of life based on personal characteristics; 3) work-related factors such as work progress, job characteristics, and aspects of policy and administration had a statistically significant effect on quality of life at the 0.05 level; and 4) several guidelines were proposed to enhance quality of life, focusing on physical health, stress management, teamwork, workplace and accommodation conditions, career development, and the implementation of clear and comprehensive policies.